IMPLEMENTASI KEBIJAKAN PEMERINTAHAN PROVINSI DKI JAKARTA SEBAGAI IBUKOTA NEGARA INDONESIA - Yunus, Muhamad; Prabowo, Hadi; Nuryanto, Nuryanto (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
The purpose of writing this research is to find out and analyze the implementation of Article 33 of Law Number 29 of 2007 concerning the Provincial Government of the Special Capital Region of Jakarta as the Capital of the Unitary State of the Republic of Indonesia in relation to funding, to analyze the supporting and inhibiting factors for the implementation of the DKI Jakarta Provincial Government policies which relation to funding, and analyze the work structure to overcome the inhibiting factors rather than the implementation of DKI Jakarta Provincial Government policies in the context of funding. The method used is qualitative-descriptive which produces descriptive data in the form of speech or writing and observable behavior from people (subjects). The results of the study reveal that there are no detailed rules or mechanisms for the implementation of the DKI Jakarta policy as the State Capital of the Republic of Indonesia in the context of the funding of Law Number 29 of 2007 concerning the Provincial Government of the Special Capital Region of Jakarta as the Capital of the Unitary State of the Republic of Indonesia. In addition, there is an increase in human resources in the DKI Jakarta Provincial Government as reflected in the issuance of the Governor's Regulation No. 58 of 2021 Regarding the Road Map for Bureaucratic Reform in 2020-2024, it will be easier to realize a clean and accountable bureaucracy, a capable bureaucracy, and a bureaucracy that has excellent public services. Efforts to spread responsibility and authority in the context of funding to DKI Jakarta Province discuss more about the mechanism for distribution and synchronization of the implementation of the RAPBD submission to the central government as well as the technicalities in the preparation of the APBD in accordance with applicable laws and regulations.